Role of CBC Parameters in COPD with Acute Exacerbation in a Tertiary Care Center - Pudasaini, S; Adhikari, P; Maharjan, S; Jha, AK; Dhakal, N (Nepal Medical College Journal, 2019)
Chronic obstructive pulmonary disease (COPD) is a major global health problem. It is a complex disease characterised by chronic inflammation in the airways by noxious particles. Episodes of increased symptoms called as acute exacerbations are associated with accelerated decline in the lung function. Blood cultures to find out the causative organism in these cases are time consuming. Complete Blood Count (CBC) parameters like Total leukocyte count (TLC), hemoglobin (Hb), platelet count, Mean Platelet Volume (MPV), Platelet Distribution Width (PDW) are found to be related with COPD and its acute exacerbation. An observational hospital based descriptive study was conducted for a period of six months in the Department of Pathology and Medicine of a tertiary care centre. A total of 144 patients of COPD with acute exacerbation (AECOPD) were included in the study. The mean age of the patients was 70.47 ± 9.49 years with female preponderance (61.1%). Though mean hemoglobin level (13.25 ± 2.70 gm %), (95% CI 12.80-13.69) showed statistical significance, other CBC parameters had no obvious difference among the different groups of AECOPD patients. But we cannot deny on the clinical significance of these parameters. The TLC and platelet count were slightly lower in the AECOPD patients with cor pulmonale when compared with AECOPD patients without cor pulmonale. Similarly, platelet parameters like MPV and PDW were slightly higher in the AECOPD patients who are smokers. Though these parameters were not statistically significant, they are found to be cost effective, time saving and clinically significant which would definitely help in the management of AECOPD patients. Hence, these parameters can be used as an easily measurable AECOPD biomarker.